The effect of double (S238F/W159H) mutations on the structure and dynamics of PET degrading enzyme - Mhashal, Anil Ranu; Kumar T, Neeraj; Kumar, Nitheeshkumar; Singhal, Anshul; Ravandur, Akash; Sokkar, Pandian; Kulkarni, Naveen (Journal of biomolecular structure & dynamics, 2025)
Polyethylene terephthalate (PET) is one of the highly produced synthetic polymers worldwide and had acquired attention due to its impact resistance, high clarity, and light weight. PET has become the first choice in making disposable bottles, leading to massive scales of production resulting in very high utilization across various facets of our daily life. Unfortunately, PET accumulates as waste and is highly resistant to biodegradation, thus presenting a serious threat to the ecosystem. Degradation of PET by enzymatic hydrolysis is a promising strategy to depolymerize the PET into its monomers. In recent studies, a plastic-degrading enzyme known as PETase (IsPETase) from the Ideonella sakaiensis has been identified to hydrolyze PET. The wild-type enzyme from Ideonella sp., has been engineered to improve the catalytic activity. While the IsPETase and its variants have been the subject of extensive structural and biochemical studies, the corresponding computational studies to support the improved activity of the mutant enzyme is not fully understood. In this work, we employed all-atom classical molecular dynamics simulations of the wild-type and double mutant IsPETase enzymes to investigate the underlying reason for the improved catalytic activity in the double mutant by means of structure-dynamics-function relationship. Our results show that the engineered mutations reshape the active site structure, volume, and dynamics of the protein loops which is crucial for substrate binding. We also demonstrate that addition of aromatic and hydrogen bond-forming residues near catalytic site improves binding affinity. This work will enable the rational design of mutants for enhanced PET degrading activity.